Renal Function Follow-Up and Renal Recovery After Acute Kidney Injury in Critically Ill Children*. Issue 8 (August 2017) - Hessey, Erin; Ali, Rami; Dorais, Marc; Morissette, Geneviève; Pizzi, Michael; Rink, Nikki; Jouvet, Philippe; Lacroix, Jacques; Phan, Véronique; Zappitelli, Michael
Abstract : Objectives: To evaluate factors associated with renal recovery from acute kidney injury in critically ill children and the extent to which serum creatinine is measured before discharge. Design: Retrospective cohort study. Setting: Two PICUs at tertiary centers in Montreal, QC, Canada. Patients: Children (< 18 yr old) admitted to the PICU between 2003 and 2005. Patients with end-stage renal disease, no healthcare number, died during admission, or admitted postcardiac surgery were excluded. Interventions: None. Measurements and Main Results: Acute kidney injury was defined using internationally accepted criteria (Kidney Disease: Improving Global Outcomes). Two renal recovery outcomes commonly used in the literature were evaluated: hospital discharge serum creatinine less than 1.5 and less than 1.15 times baseline. Proportions of patients with 1) serum creatinine measurements between PICU and hospital discharge and 2) renal recovery were calculated. Univariate and multivariate analyses were performed to determine factors associated with serum creatinine monitoring and nonrecovery after acute kidney injury. Of 2, 033 patients included, 829 (40.8%) had serum creatinine measurements between PICU and hospital discharge. The odds of having a discharge serum creatinine measurement increased with acute kidney injury severity (stages 1, 2, 3 adjusted odds ratio [95% CI]: 1.49 [1.03–2.15], 2.52 [1.40–4.54], 7.87 [3.16–19.60], respectively). Acute kidney injury recovery was 92.5% when defined as serum creatinine less than 1.5 times baseline versus 75.9% when defined as less than 1.15 times baseline ( p < 0.001). Stage 3 acute kidney injury was associated with having a discharge serum creatinine greater than or equal to 1.5 times baseline (adjusted odds ratio = 3.51 [1.33–9.19]). Conclusions: Less than half the PICU population had serum creatinine measured before hospital discharge. More severe acute kidney injury was associated with higher likelihood of serum creatinine monitoring and lower probability of acute kidney injury recovery. Future research should address knowledge translation on post-PICU acute kidney injury follow-up before hospital discharge.